Characterization of Red Melinjo (Gnetum gnemon L.) Extract as Antibacterial Compound - Angel, Veliana; Parhusip, Adolf; Cendrawan, Yusuf (JURNAL AGROINDUSTRI HALAL, 2026)
Melinjo (Gnetum gnemon L.) is one of the native plants in Southeast Asia, including Indonesia. Melinjo peel is generally disposed of, even though it contains bioactive compounds such as tannin, flavonoid and saponin, which can be used as antimicrobial compounds. The purpose of this research was to analyze the antimicrobial activity of Melinjo peel extract. The extraction of red melinjo peel was conducted by the maceration method using ethyl acetate as solvent for 24 h at room temperature. The extract at concentration (4-16% (w/v) could inhibit the growth of Escherichia coli ATCC 8739, Bacillus cereus ATCC 10876, and Pseudomonas aeruginosa ATCC 9027 but not Rhizopus oligosporus ATCC 22959. The Minimum Inhibitory Concentration (MIC) of the extract ranged from 0.50-0.69%, while the Minimum Bactericidal Concentration (MBC) value ranged from 2.00-2.76%. The inhibitory capacity of the extract at selected concentration (12%) had a similar level as compared to 1000 ppm Colistin against E. coli and P. aeruginosa. The inhibition of extract increased at pH 4 but decreased neutral pH. Heat treatment at 65oC for 30 minutes increased the antibacterial activity but decreased at 75-95oC. Addition of salt and sugar at concentration 1-5% and 10-50%, respectively also increased the antibacterial activity of the extract